How Whatsapp Business E-Service Quality and Brand Reputation Influence Purchase Intentions? Empirical Finding Events Demand in Bali - I Gede Sumadi; Ni Kadek Swandewi; I Gusti Ayu Ratih Asmarani; I Nengah Wirata; Luh Putu Citrawati (Eduvest - Journal of Universal Studies, 2025)
The rapid adoption of digital communication tools, particularly WhatsApp Business, has transformed the event services industry by enhancing e-service quality and customer engagement. Despite its growing popularity, research on how WhatsApp Business influences e-service quality and purchase intention remains limited. This study examines the impact of e-service quality and brand reputation on purchase intentions for event services in Bali, addressing a critical gap in the literature. Using Structural Equation Modelling (SEM) with PLS algorithm and bootstrapping techniques, data were collected from 100 respondents who had previously purchased event services. The findings reveal a strong, statistically significant relationship between e-service quality and purchase intention (original sample value = 0.751, p-value = 0.000), highlighting the importance of responsiveness, efficiency, and personalization. However, brand reputation’s mediating role was weak (original sample value = 0.195, p-value = 0.030), suggesting it does not significantly alter the direct influence of e-service quality. These results underscore the primacy of e-service quality in driving purchase decisions, offering practical insights for event organizers to optimize WhatsApp Business for customer satisfaction and loyalty. The study contributes to the broader understanding of digital service quality in the event industry and provides actionable strategies for leveraging technology to enhance consumer experiences.